A Review on Natural Fiber Reinforced Polymer Composites - R, Noor Ahmed.; M.R, Chethan.; S, Suraj.; Krishna, S. G. Gopala (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
FRP’s have huge applications in the field of Automobile, Aerospace, Military applications, Building and Construction Industries (ceiling, paneling and partition boards) Etc. These applications are due to its low weight and high mechanical properties. Fiber Reinforced Polymer composite have a very dominant role in variety of applications for their high specific strength and modulus. Lot of work is carried by various researches with different reinforcements. The reinforcement used in various applications are Fibers of Glass, Carbon, Aramid, Asbestos and Kevlar fibers. Since the natural reinforcements have less side effect and abduantly available, Lot of researches reviewed with natural reinforcements for various applications in the form of sheets, boards etc. Due to the limitations of synthetic fibers as reinforcement the use of FRP composite increased the interest of researches. The mechanical properties of a natural fiber reinforced composite depend on parameters like fiber strength, fiber length, chemical treatment and orientation in addition to fiber-matrix interfacial bond strength. Here this review article is taken as natural fiber reinforcement for development of composites.